Emission factors of ammonia for on-road vehicles in urban areas from a tunnel study in south China with laser-absorption based measurements. (1st July 2021) - Li, Sheng; Liu, Tengyu; Song, Wei; Pei, Chenglei; Huang, Zuzhao; Wang, Yujun; Chen, Yanning; Yan, Jianhong; Zhang, Runqi; Zhang, Yanli; Wang, Xinming
Abstract: Vehicle emission is an important source of ammonia (NH3 ) in urban areas. To better address the role of vehicle emission in urban NH3 sources, the emission factor of NH3 (NH3 -EF) from vehicles running on roads under real-world conditions (on-road vehicles) needs to update accordingly with the increasingly tightened vehicle emission standards. In this study, laser-absorption based measurements of NH3 were conducted during a six-day campaign in 2019 at a busy urban tunnel with a daily traffic flow of nearly 40, 000 vehicles in south China's Pearl River Delta (PRD) region. The NH3 -EF was measured to be 16.6 ± 6.3 mg km −1 for the on-road vehicle fleets and 19.0 ± 7.2 mg km −1 for non-electric vehicles, with an NH3 to CO2 ratio of 0.27 ± 0.09 ppbv ppmv −1 . Multiple linear regression revealed that the average NH3 -EFs for gasoline vehicles (GVs), liquefied petroleum gas vehicles, and heavy-duty diesel vehicles (HDVs) were 18.8, 15.6, and 44.2 mg km −1, respectively. While NH3 emissions from GVs were greatly reduced with enhanced performance of engines and catalytic devices to meet stricter emission standards, the application of urea selective catalytic reduction (SCR) in HDVs makes their NH3 emission an emerging concern. Based on results from this study, HDVs may contribute over 11% of the vehicular NH3 emissions, although they only share ∼4% by vehicle numbers in China. With the updated NH3 -EFs, NH3 emission from on-road vehicles was estimated to be 9 Gg yr −1 in the PRD region in 2019, contributing only 5% of total NH3 emissions in the region, but still might be a dominant NH3 source in the urban centers with little agricultural activity. Graphical abstract: Image 1 Highlights: Emission factors of NH3 for on-road vehicles dropped dramatically during 2013–2019. Emission factors of NH3 for each fuel-types derived via multiple linear regression. Stricter emission standards facilitate reducing NH3 from gasoline vehicles. Heavy-duty diesel vehicles contribute significantly to NH3.